Role of cyano substituents on thiophene vinylene benzothiadiazole conjugated polymers and application as hole transporting materials in perovskite solar cells - K. Mahesh (2018)
© 2018 Elsevier B.V. Two narrow-band gap of donor-acceptor based conjugated polymers, BTTP and BTTP-CN were synthesized by Wittig copolymerization with thiophene or cyano-vinylene thiophene as the donor and 2,1,3-benzothiadiazole as acceptor units. The polymers were investigated by FT-IR, UV-V is, fluorescence spectroscopy, thermal stability and cyclic voltammetry (CV). The thermal analysis revealed that the BTTP polymer was stable up to 220 °C and BTTP-CN was stable up to 254 °C. The absorption spectra showed absorption maxima at 403 nm for BTTP and 397 nm for BTTP-CN. The polymers BTTP exhibited orange colour fluorescence emission at 585 nm and BTTP-CN exhibited yellow color fluorescence emission at 520 nm. The optical band gap values of undoped polymers BTTP and BTTP-CN were calculated as 2.2 and 2.13 eV respectively. Novel synthesized polymers were then enforced as dopant/additive-free hole transport materials in perovskite solar cells. Both polymers has shown the photovoltaic performance of 3.80 % for BTTP and 3.48 % for BTTP-CN under 1 sun illumination. The photovoltaic performance are compared with reference hole transporting material of spiro-OMeTAD with and without additive as 12.53 and 7.55% respectively.